If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2=-1+y
We simplify the equation to the form, which is simple to understand
-2=-1+y
We move all terms containing y to the left and all other terms to the right.
-1y=-1+2
We simplify left and right side of the equation.
-1y=+1
We divide both sides of the equation by -01 to get y.
y=-1
| 8x-4x+8=20+4 | | -2x-47=-47 | | 4a-3y= | | 0.25x-4=7 | | 6b-b+3=b+5b | | 4t-2(3t-4)=10 | | 6-2r+r=2-3r | | B=rw+r | | 4x-50=8 | | -8y-2=-9-3y | | 3/4(z)=-18 | | x^2+2x+42=0 | | -8=k-11 | | y=3.8x | | 2n-6=6-2n | | p=r | | 55=6*8+7 | | 3y=-2x-1 | | -14x^2-29x-12=0 | | 47.582-0.01(0.2+3x)=7.9x | | M=150+38x | | m-7=-10 | | 0=-8p-6p | | 10=v/2 | | -x-8=2y | | 39=-4x-1 | | -5(x-1)+6= | | 75x^2+65x+10=0 | | 19=m+7-3m | | -12+5k=15-14k | | 30d+12=18d | | 19=9x-8 |